PENGARUH KOMPETENSI DAN QUALITY OF WORK LIFE TERHADAP KINERJA MELALUI KEPUASAN KERJA - Kusumastuti, Erna; Priyono, Bambang Suko (MANAJEMEN DEWANTARA, 2024)
The purpose of this study was to test and analyze the effect of competence and QWL on performance by mediating job satisfaction (Study on Employees of the Kendal Education and Culture Office). The sample in this study were 101 respondents. This research test consists of descriptive statistics, instrument test (validity test with KMO>0.5 and Loading Factor>0.4 and reliability test with Cronbach alpha>0.7), model test (Adj R2 Test (Coefficient of Determination) and F Test (Goodness of Fit) with sig level <0.05), hypothesis testing using regression analysis with sig level <0.05 and test mediation effect with sobel test. The results of this study indicate that competence and QWL affect job satisfaction both partially and simultaneously. Furthermore, competence, QWL and job satisfaction have a positive and significant relationship to performance.